Estimadores robustos e concentração de medida: uma introdução - Monteiro, Adriana Laurindo (2021)
This dissertation presents important results on high dimension probability and on robust statistics. Statistics functionals and its perfomances and derivatives, as well as subgaussian stochastics process are some of the topics. Besides that, we present an application in classification problems, a subject in statistical learning theory. The main results are a central limit theorem of a covariance function robust estimator and Dudley’s Inequality (Dudley’s entropy integral).